Investigating the Perceptions of Primary School Students on Gamification-based Learning in Mathematics: A Descriptive Survey Study - Rahim, Mujeebur; Mohamed, Lubna Ali; Haq, Shams ul (Pakistan Journal of Humanities and Social Sciences, 2024)
The main focus of this study is to investigate student perceptions about integrating gamification-based learning into the primary level of mathematics, specifically discussing teaching related to the example Kahoot framework. A descriptive survey design was used, targeting 27 5th-grade students from Boys High School Gorikote, who had previous engagement with or learning through gamification. The research sample was selected using a purposive sampling method. The data was gathered using a standardized questionnaire derived from prior research and verified by professionals. The data was assessed using descriptive statistics such as frequency, mean, and standard deviation. The analysis of data showed that over 90% of the students had a strong consensus on the efficacy and applicability of Kahoot in enhancing mathematics skills and conceptual understanding and providing a good learning experience. Learning with Kahoot was enjoyable, effective, and favourable to collaboration and teacher-student interaction. This study highlighted Kahoot's transformative potential at the primary level of mathematics education, with a key role being played in its fostering of motivation, engagement, and academic performance. Considering the students' positive perceptions of Kahoot and its effectiveness in facilitating mathematical skills and conceptual understanding, it is recommended that Kahoot or a similar gamification-based learning tool be integrated into primary mathematics education in district Astore Gilgit Baltistan (where internet access and IT labs are available).